GAYA KEPEMIMPINAN, PROFESIONALITAS, DAN ETOS KERJA PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA KARYAWANPADA THE TRANS HOTEL KUTA - Tettie Setiyarti; I Gusti Ayu Putu Andayani; Ida Bagus Radendra Suastama (Forum Manajemen, 2020)
Managerial and leadership skills possessed by a leader are needed in processing human resources in optimizing employee performance, because employees are one of the important assets to realize the organization's vision and mission. In this paper, the writer tries to find a gap or mismatch between expectations and reality (Das Solen Das Sein) between leadership style and facts on the ground, using The Trans Resort Hotel, Kuta, as the locus of the whole discussion. This paper will discuss descriptively the hotel’s leadership style, its employees’ professionalism and work ethics, and their effects on productivity of the hotel. Data collection methods were done through observation, interviews, and documentation, while the analysis technique used include the classic assumption test, multiple linear regression and hypothesis testing. The results of this study indicate that leadership, professionalism, and work ethic have a positive and significant effect in influencing the level of work productivity of employees who work in The Trans Hotel Kuta, Bali.